Step 1: find the slope using the slope formula.
m = (y2 - y1) / (x2 - x1)
(x1,y1) = (1, 2)
(x2,y2) = (4, 6)
m = (6 - 2) / (4 - 1) = 4/3
Step 2: Now that we have the slope, reuse the slope formula to get the equation of the line. This time, use (1, 2) and (x, y) as (x1, y1) and (x2, y2)
(y2 - y1) / (x2 - x1) = m
But the difference is, we have the slope now. m = 4/3.
(y - 2) / (x - 1) = 4/3
Cross multiplying,
3(y - 2) = 4(x - 1)
3y - 6 = 4x - 4
Moving everything over to the right hand side,
0 = 4x - 3y + 2
2007-01-27 04:15:21
·
answer #1
·
answered by Puggy 7
·
1⤊
0⤋
An equation for a line passing thru (1, 2) and (4, 6) is
(y-y1)/(x-x1) = (y2-y1)/x2-x1)
(y-2)/(x-1) = (6-2)/(4-1) = 4/3
y-2= 4/3(x-1)
y = 4/3x-4/3+2 = 4x/3-2/3
3y = 4x -2
4x-3y -2 = 0
2007-01-27 04:25:45
·
answer #2
·
answered by ironduke8159 7
·
0⤊
0⤋
By using the formula: (y-y1)/(y2-y1)=(x-x1)/(x2-x1)
y-2/6-2=x-1/4-1
y-2/4 =x-1/3
3y-6 =4x-4
4x-3y+2=0
2007-01-29 01:40:10
·
answer #3
·
answered by laminewton 2
·
0⤊
0⤋
The slope m of the line: m = distinction in Y-coordinates/ distinction of X-coordinates =(-2+6)/(one million-4) = - 4/3. The equation of the line is y-b =m(x-a). right here, y+2 = (- 4/3)(x-one million) Or 3y +6 = - 4x +4. which leads to : 4x+3y +2 =0. answer. ensure: ok
2016-11-27 22:11:43
·
answer #4
·
answered by ? 4
·
0⤊
0⤋
y=mx+b
m=rise/run = (6-2)/(4-1) = 4/3
so y = 4/3x + b
Plug in values of x and y from one of the points (1,2):
2 = 4/3(1)+b
b=2-4/3 = 2/3
y = 4/3x + 2/3
multiply by 3:
3y = 4x + 2
so
0 = 4x - 3y + 2
2007-01-27 04:16:42
·
answer #5
·
answered by J 2
·
0⤊
0⤋
y=mx+b
m=slope=rise/run
rise=6-2=4
run=4-1=3
m=4/3
now use y=mx+b to find b
(4,6)
6=(4/3)(4)+b
6=16/3+b
18/3-16/3=b
2/3=b
y=(4/3)x+(2/3)
To choose between the options, you need to remove the fraction which you can do by multiplying all the terms by 3
3(y)=(3)(4/3)x+(3)(2/3)
3y=4x+2
4x-3y+2=0
2007-01-28 12:34:03
·
answer #6
·
answered by Michelle M 2
·
0⤊
0⤋
using two point formula,
(y-y1)/(x-x1)= (y2-y1)/(x2-x1)
assume y1=2 ;x1 =1; y2=6; x2=4
(y-2)/(x-1)=(6-2)/(4-1)
(y-2)/(x-1)= 4/3
3y-6 = 4x-4
4x-3y-2=0
Ans: Equation of line is 4x-3y-2=0
2007-01-27 04:15:27
·
answer #7
·
answered by ? 5
·
0⤊
0⤋